Effects of Android-Based Sayang ke Buah Hati (SEHATI) Application towards Mothers’ Knowledge and Children’s Skill on Hand Washing with Soap - Yopi Suryatim Pratiwi; Heda Melinda Nataprawira; Bambang Sasongko Noegroho; Farid Husin; Dewi Marhaeni Diah Herawati; Julistio T.B. Djais (Global Medical & Health Communication (GMHC), 2019)
Hand washing with soap is the most straightforward skill that elementary school-aged children should have to avoid infectious disease transmission. Rapid development of today’s technology has led to efforts to develop android-based applications for smartphones to improve health-related knowledge. Sayang ke Buah Hati (SEHATI) application is an android-based application for improving mother’s knowledge on health-related issues. The objective of this study was to analyze the effects of SEHATI application in improving mothers' knowledge regarding hand washing and the relationship between mothers' knowledge and children's skills improvement in hand washing with soap. This was a quasi-experimental study with pretest-posttest one group design conducted in the period of February to March 2017 on 33 mothers and students of grades 1 and 2 of Uchuwwatul Islam Elementary School in Bandung city who met the inclusion criteria, not met exclusion criteria, and are willing to participate as respondents. Knowledge data were analyzed using paired t test while skill data were analyzed using Spearman rho. Results showed that SEHATI application improved mothers' knowledge on hand washing with soap (p<0.001). A relationship was observed between mothers' knowledge and improved children's skill in hand washing with soap (p<0.001). It is concluded that SEHATI application can be used as a guide for parents to find health-related information, which improves mother's knowledge on hand washing with soap and indirectly improves children's skill in hand washing with soap. PENGARUH APLIKASI SAYANG KE BUAH HATI (SEHATI) BERBASIS ANDROID TERHADAP PENGETAHUAN IBU DAN KETERAMPILAN ANAK TENTANG CUCI TANGAN PAKAI SABUNMencuci tangan menggunakan sabun merupakan keterampilan paling sederhana yang harus dimiliki anak usia sekolah dasar untuk mencegah penyakit menular. Perkembangan teknologi yang berkembang pesat saat ini merupakan salah satu upaya meningkatkan pengetahuan ibu, yaitu dengan memanfaatkan aplikasi Sayang ke Buah Hati (SEHATI) yang tersimpan dalam smartphone android. Tujuan penelitian menganalisis pengaruh penerapan aplikasi SEHATI berbasis android pada ibu terhadap peningkatan pengetahuan tentang cuci tangan pakai sabun dan hubungan antara pengetahuan ibu dan keterampilan anak tentang cuci tangan pakai sabun. Penelitian menggunakan metode quasi-experiment dengan pretest-posttest one group design. Subjek penelitian adalah 33 ibu dan anak kelas 1 dan 2 SD Uchuwwatul Islam di Kota Bandung yang telah memenuhi kriteria inklusi dan tidak termasuk kriteria eksklusi serta bersedia menjadi responden. Penelitian ini dilakukan pada bulan Februari sampai Maret 2017. Analisis data pengetahuan menggunakan uji t berpasangan, sedangkan analisis data keterampilan menggunakan Spearman ro. Hasil penelitian menunjukkan bahwa aplikasi SEHATI meningkatkan pengetahuan ibu tentang cuci tangan pakai sabun (p<0,001). Terdapat hubungan antara pengetahuan ibu dan keterampilan anak tentang cuci tangan pakai sabun (p<0,001). Simpulan, aplikasi SEHATI dapat digunakan sebagai panduan orangtua dalam mencari informasi kesehatan yang mampu meningkatkan pengetahuan ibu serta berdampak pada keterampilan anak tentang cuci tangan pakai sabun.